Proceedings of the 2015 International Symposium on Material, Energy and Environment Engineering 2015
DOI: 10.2991/ism3e-15.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study of the Influence of Flue Gases Recirculated on NOx Emissions

Abstract: Abstract. Flue gas recirculation is considered to be one of the most promising and cost-effective NO x reduction strategies for combustion systems. Therefore, it has great scientific and practical significances to investigate the flue gas recirculation process. Fluent was used to perform a numerical flue gas recirculation simulation on natural gas combustion in a burner, revealing the relationship between NO x emission and circulation ratio, circulation temperature, and circulation locations. The following con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Li et al discovered that there is an enhancement of nitrogen oxide formation for pressures lower than 5 atm with the recirculated gas method (constant flame temperature). ElKady et al , found that NOx emission declined more than 50% with 35% flue-gas recirculation in a depleted premixed flame of CH 4 under 10 atm (constant flame temperature). The formation of NOx is confirmed to be impacted by the recirculation flue-gas ratio. Yue et al confirm that a larger recirculation flue-gas proportion inside the reactor is conducive to better stability of the combustion manner in a certain range. Therefore, it is a challenge to stabilize the oxidation in small-scale systems due to the high heat losses and the uncontrollable recirculation flue-gas proportion.…”
Section: Impact Of Factors On Nox Reduction and Combustion Performancementioning
confidence: 97%
See 2 more Smart Citations
“…Li et al discovered that there is an enhancement of nitrogen oxide formation for pressures lower than 5 atm with the recirculated gas method (constant flame temperature). ElKady et al , found that NOx emission declined more than 50% with 35% flue-gas recirculation in a depleted premixed flame of CH 4 under 10 atm (constant flame temperature). The formation of NOx is confirmed to be impacted by the recirculation flue-gas ratio. Yue et al confirm that a larger recirculation flue-gas proportion inside the reactor is conducive to better stability of the combustion manner in a certain range. Therefore, it is a challenge to stabilize the oxidation in small-scale systems due to the high heat losses and the uncontrollable recirculation flue-gas proportion.…”
Section: Impact Of Factors On Nox Reduction and Combustion Performancementioning
confidence: 97%
“…(3) The formation of NOx is confirmed to be impacted by the recirculation flue-gas ratio. 65−72 Yue et al 71 confirm that a larger recirculation flue-gas proportion inside the reactor is conducive to better stability of the combustion manner in a certain range. Therefore, it is a challenge to stabilize the oxidation in small-scale systems due to the high heat losses and the uncontrollable recirculation flue-gas proportion.…”
Section: Impact Of Factors On Nox Reduction and Combustion Performancementioning
confidence: 99%
See 1 more Smart Citation